The Impact of Effriction and Frirage Massage Techniques on Pain and Range of Motion Improvement in Knee Injuries - Hasan, Cahulul Rizaldy; Setiawan, Arif; Akhiruyanto, Andry (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2025)
Introduction: Daily physical activities, especially sports, always contain the risk of injury, which most often occurs in the lower extremities, especially the knee joint. Knee injuries are generally caused by direct trauma, excessive pressure, or incorrect movement techniques, resulting in clinical symptoms such as pain, swelling, and decreased range of motion that can interfere with daily activities. Many athletes and the general public experience this problem, so proper and fast treatment is needed. Purpose: This study aims to evaluate the effectiveness of two massage methods, namely effriction and frirage in treating knee injuries with a 2x2 factorial experimental design. Method: The study sample was purposively selected and then divided into four groups based on the type of massage and duration of injury (10 days and 1 month). Two main parameters were measured: pain level using a Visual Analogue Scale (VAS) and joint range of motion using a Goniometer. Data were analysed using SPSS through normality, homogeneity, and Two-Way ANOVA tests to test for differences in treatment effects. Results: The results showed that effriction was more effective in reducing pain at 1 month (58.33%) compared to 10 days (44.44%), while frirage was optimal in the initial phase (34.92%). ROM improvement was more significant on long-term therapy (effriction: 21.64%; frirage: 18.24%). Two-way ANOVA analysis revealed a significant interaction between the massage method and the duration of injury (p<0.05). Conclusion: The selection of massage technique should consider the duration of injury, with effriction for long-term treatment and frirage for the acute phase for optimal rehabilitation outcomes.